Handbook of analytic philosophy of medicine - Sadegh-Zadeh, Kazem (Philosophy and Medicine, 2012)
Medical practice is practiced morality, and clinical research belongs to normative ethics. The present book elucidates and advances this thesis by: 1. analyzing the structure of medical language, knowledge, and theories; 2. inquiring into the foundations of the clinical encounter; 3. introducing the logic and methodology of clinical decision-making; 4. suggesting comprehensive theories of organism, life, and psyche; of health, illness, and disease; of etiology, diagnosis, prognosis, prevention, and therapy; and 5. investigating the moral and metaphysical issues central to medical practice and research.